Demokrasi dan Ketimpangan Pendapatan: Analisis Data Panel 9 Negara ASEAN Tahun 1973-2020 - Zahran Ramadhan (Universitas Diponegoro, 2023)
Studies on democracy and income inequality have produced diverse findings. There are still many limitations in the study of democracy and inequality, both methodologically and empirically. Many empirical studies discuss the relationship over the years with observations in multiple countries. Krauss (2015) argues that analyzing democracy and inequality through specific regions will yield deeper and more robust results. This research examines the relationship between democracy and income inequality using panel data from 9 ASEAN countries over the period from 1973 to 2020. Fixed effects panel data modeling and the democracy index published by Freedom House were used. The study finds a significant relationship between democracy and income inequality, indicating that more democratic countries tend to experience increased income inequality. Based on these findings, democracy in ASEAN has not yet reached the point of institutionalized democracy or the phase where democracy would reduce income inequality. This research attempts to offer contextual explanations and mechanisms that may lead to these findings for the ASEAN region.